2017
DOI: 10.1136/jfprhc-2017-101740
|View full text |Cite
|
Sign up to set email alerts
|

Quick starting hormonal contraception after using oral emergency contraception: a systematic review

Abstract: Three randomised controlled trials were identified. Two biomedical studies suggested HC action was unaffected by quick starting after UPA; one study examined ovarian quiescence (OR 1.27; 95% CI 0.51-3.18) while taking combined oral contraception (COC). Another assessed cervical mucus impenetrability (OR 0.76; 95% CI 0.27-2.13) while taking progestogen-only pills (POP). Quick starting POP reduced the ability of UPA to delay ovulation (OR 0.04; 95% CI 0.01-0.37). Side effects (OR 1.22; 95% CI 0.48-3.12) and unsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recommendations are more complex following use of UPA given concerns that UPA may interact with other forms of hormonal contraceptive due to its role as a progesterone receptor modulator . A recent systematic review of commencing hormonal contraception following EC use identified limited studies on which to base treatment recommendations, but did find evidence to suggest that initiation within 5 days of UPA use may negatively impact on its ability to delay ovulation, exposing women to the same risk of pregnancy faced without use of EC . Therefore, if UPA is used then alternative hormonal contraception should not be commenced for 5 days, at which point an additional barrier method of contraception should be used until contraceptive cover is provided.…”
Section: Ongoing Contraceptionmentioning
confidence: 99%
“…Recommendations are more complex following use of UPA given concerns that UPA may interact with other forms of hormonal contraceptive due to its role as a progesterone receptor modulator . A recent systematic review of commencing hormonal contraception following EC use identified limited studies on which to base treatment recommendations, but did find evidence to suggest that initiation within 5 days of UPA use may negatively impact on its ability to delay ovulation, exposing women to the same risk of pregnancy faced without use of EC . Therefore, if UPA is used then alternative hormonal contraception should not be commenced for 5 days, at which point an additional barrier method of contraception should be used until contraceptive cover is provided.…”
Section: Ongoing Contraceptionmentioning
confidence: 99%